Jenis Frasa dalam Teks Berita CNBC Indonesia Terbitan Agustus 2025 - Ananda Syinta Panca Rani; Gracia Natalia Maketake; Ineke Lulu Septia Rahmadhani; Khairunissa Andarenwi Nugroho; Mikhail Aimran Shobirin; Asep Purwo Yudi Utomo; Zulfa Fahmy; Dyah Prabaningrum (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of information technology has pushed the dissemination of news through online media, demanding a language that is fast, concise, and informative to ensure accurate news delivery. This necessity positions the syntactic structure, particularly the phrase, as a critical element in determining the quality and communication effectiveness of digital news. This study has a dual objective: to comprehensively identify and analyze the types of phrases found in five online news articles published by CNBC Indonesia in August 2025, and to elucidate the grammatical function of each phrase within the context of news sentences. The method employed is a descriptive qualitative method, involving a systematic process of reading, noting, and accurately analyzing the textual data repeatedly. The results indicate a diversity of phrase types, with a significant dominance of noun and verb phrases. The findings also include adjectival, prepositional, adverbial, numerical, exocentric, and endocentric phrases, which collectively enrich the linguistic structure, enhance information richness, and greatly facilitate reader comprehension of the news content. These findings not only highlight the specific patterns of phrase usage in digital news writing but also provide deep insights into their structural and grammatical roles. This study is expected to serve as a valuable reference for linguistic research and language learning, as well as offering practical guidance for online media practitioners to continuously improve the clarity, effectiveness, and quality of news writing in the digital realm.